FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN UNDERWEIGHT PADA BALITA DI WILAYAH PEDESAAN KABUPATEN DEMAK - Ari Setyowati; Sunarto Sunarto; Sri Noor Mintarsih (Poltekkes Kemenkes Semarang, 2016)
Background: The prevalence of underweight children in Demak Regency was 21%, the percentage was over the data from Central Java. Underweight will hamper the cognitive and motor development to children with a negative impact to the future. This study aims to determine the correlation between energy and protein intake, disease, parenting, attitude, knowledge, education, occupation and income with the underweight. Methods: The data used in this research is Basic Data Collecting (PDD) of Polytechnic of Health Ministry of Health Semarang. This study is an explanatory research with cross sectional design. The sampling was carried out at random (random sampling) to get 420 children as sample aged 0-59 months. Nutrition Factor (energy and protein) was gotten by Food Recall for 3 x 24 hours, Disease history factor, Parenting factors (parenting, attitudes, knowledge) and socioeconomic factors (education, occupation and income) were obtained using a questionnaire with interview methode. The Analytic analysis used chi – square test. Results: There was no correlation between intake of energy, protein intake, maternal parenting, maternal attitude, maternal knowledge, maternal education, maternal occupation, maternal income with underweight, and there is a significant correlation between children infectious disease history with underweight problem at p = 0.047 (p 0.05) OR = 1.6. Conclusion: There is significant correlation between the disease history and underweight. Need to do weight measurements regularly to observe the underweight problem to children in posyandu